An Analysis Perspective Implemented Text Mining Analytics Information Extraction For Impect of Indonesian Social Media - Agus Suryana; Sri Ipnuwati (Bandar Lampung University (UBL), 2014)
The development and growth of the Indonesian nation-building which consists of various cultures and religions changed the way the public life of the state and the nation of Indonesia. Social media plays an important role in the ideological aspect, the social aspect, cultural aspect, the religious aspects, and aspects of defense and security of the ethnic diversity of the community. Social media is the social interaction among people in which they create, share or exchange information and ideas in virtual communities and networks. While the future of social media is uncertain, current trends suggest that there they will become increasingly widely adopted. Our research focuses on the perspective of the influence of social media and the development of those aspects that affect the people of Indonesia by using text mining and information extraction.